Design of Monopole Antenna Based on Fractal Geometry - Zhao Yuanqing; Qiu Jinghui; Wang Wei (International Journal of Antennas and Propagation)
This paper presents a circular disc monopole antenna based on fractal geometry. The antenna is designed to be applied in UWB systems. So it is essential to ensure that the bandwidth of the antenna ranges from 3.1 GHz to 10.6 GHz, that is, IEEE 802.15.3a. However, the proposed antenna has achieved working in the required bandwidth. Compared to the antennas illustrated in most similar literatures, the proposed antenna has a much smaller size, which makes the antenna possible to be integrated with portable devices. Firstly, the antenna was designed through CST Microwave Studio. Then, the antenna was fabricated according to the simulated results. At last, the comparison between the simulated results and measured results was carried out which demonstrated good consistency.